Biocompatibility evaluation of alendronate paste in rat's subcutaneous tissue - Mori, Graziela Garrido [UNESP]; Moraes, Ivaldo Gomes de; Nunes, Daniele Clapes; Castilho, Lithiene Ribeiro; Poi, Wilson Roberto [UNESP]; Manzoli Capaldi, Maria Luciana P. (Wiley-Blackwell Publishing, Inc, 2009)
Alendronate is a known inhibitor of root resorption and the development of alendronate paste would enhance its utilization as intracanal medication. Therefore, this study aimed to investigate the biocompatibility of experimental alendronate paste in subcutaneous tissue of rats, for utilization in teeth susceptible to root resorption. The study was conducted on 15 male rats, weighing similar to 180-200 grams. The rats' dorsal regions were submitted to one incision on the median region and, laterally to the incision, the subcutaneous tissue was raised and gently dissected for introduction of two tubes, in each rat. The tubes were sealed at one end with gutta-percha and taken as control. The tubes were filled with experimental alendronate paste. The animals were killed at 7, 15 and 45 days after surgery and the specimens were processed in laboratory. The histological sections were stained with hematoxylin-eosin and analyzed by light microscopy. Scores were assigned to the in. ammatory process and statistically compared by the Tukey test (P < 0.05). Alendronate paste promoted severe inflammation process at 7 days, with statistically significant difference compared to the control (P < 0.05%). However, at 15 days, there was a regression of in. ammation and the presence of connective tissue with collagen fibers, fibroblasts and blood vessels was observed. After 45 days, it was observed the presence of well-organized connective tissue, with collagen fibers and fibroblasts, and few in. ammatory cells. No statistical difference was observed between the control and experimental paste at 15 and 45 days. The experimental alendronate paste was considered biocompatible with subcutaneous tissue of rat.